A Multidimensional Scale for University Students' Academic Anxiety: Development, Validation, and Measurement Invariance - Ifdil Ifdil; Khairul Bariyyah; Paul Arjanto; Awalya Siska Pratiwi; M. Fahli Zatrahadi; Yulian Hermanus Wenno; Sawal Mahaly; Vando Kristi Makaruku (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Despite the widespread prevalence of academic anxiety among university students, existing measurement instruments often fail to adequately capture contemporary academic stressors or exhibit consistent validity across cultural and disciplinary contexts. This study developed and validated the Students’ Academic Anxiety Scale (SAAS), a multidimensional tool designed to comprehensively assess academic anxiety in diverse university populations. Scale development followed established psychometric procedures, including literature review, student interviews, and expert evaluations. A total of 631 students participated, divided into exploratory (n = 315) and confirmatory (n = 316) samples. The analyses revealed a stable three-factor structure-cognitive, physiological, and behavioral dimensions-with excellent model fit indices (CFI = 0.956, TLI = 0.949, RMSEA = 0.035, SRMR = 0.038). Internal consistency was high across all dimensions (Cronbach’s α > 0.80), while convergent and discriminant validity were confirmed. Measurement invariance across gender and academic disciplines further supported the scale’s cross-group applicability. The SAAS thus represents a psychometrically sound, culturally adaptable, and up-to-date instrument for identifying academic anxiety, facilitating early recognition and targeted interventions among university students.